The meanings of waw and its functions In the car (Journal of the College of Basic Education, 2022)
This research, tagged “the connotations of the waw and its functions in Arabic,” aims to clarify the behavior of the waw in the structure, and to reveal the connotations arising from that, and to define the functional approach achieved from this word, by linking, accusative, nominative, and prepositional, in the light of the context that motivates the article, as the This verbal link has a great impact on the cohesion of the text, and the strengthening of the bonds of relations in sentences, with the coloration of its patterns, its multiplicity of uses, the diversity of its connotations, and its characteristic in the modal meaning in the composition and structure of the text, and this is what called the grammarians to deal with its subject by research, writing and commentary, and the matter may occur in some cases. Sometimes to decide the difference in determining the factor required for the meaning and the inflectional effect in the context, which leads to codifying the rules and fixing the provisions through extrapolation.